High Prevalence of Self-Reported Exposure to Adulterated Drugs Among People Who Experienced an Opioid Overdose in Canada: A Cohort Study. (12th May 2019) - Prangnell, Amy; Fairgrieve, Christopher; Nosova, Ekaterina; DeBeck, Kora; Milloy, M.-J.; Hayashi, Kanna
Abstract: Background: In North America, rates of overdoses are increasing largely due to the adulteration of illicit drugs by illicit synthetic opioids. Objectives: We sought to examine the prevalence and correlates of self-reported exposure to adulterated drugs among people who experienced a non-fatal opioid overdose. Methods: Data were derived from three prospective cohort studies of people who use drugs in Vancouver, Canada between June and November 2016. Multivariable logistic regression analyses were used to examine the prevalence and correlates of self-reported exposure to adulterated drugs. Results: Among 117 participants who reported symptoms consistent with a non-fatal opioid overdose, 78 (66.7%) reported believing the drug was adulterated during their last overdose. Of those, 42 (53.8%) had not perceived adulteration prior to overdose. In the multivariable analysis, engagement in opioid agonist therapy (Adjusted Odds Ratio [AOR] = 2.79, 95% Confidence Interval [CI]: 1.10, 7.45) was independently associated with having not perceived adulteration prior to overdose. Daily heroin use (AOR = 5.28; 95% CI: 1.92, 15.97) and reporting supervised injection site staff were present at most recent overdose (AOR = 6.16; 95% CI: 1.25, 47.27) were independently associated with having perceived adulteration prior to overdose. Conclusions/Importance: We found a high prevalence of believing adulterated drugs were present for the most recent overdose. Further, the high prevalence of unperceived adulteration prior to overdose supports the need to lower the risk of overdose by providing individuals with options to consume drugs in a safer manner, including supervised consumption sites.